Pendidikan Keluarga dalam Membangun Karakter Anak di Sekolah: - Sulistyo Adam Rantererung (Medan Resource Center, 2021)
In the current millennium era, there are many unavoidable external influences that cause social problems. These problems have an impact on the lives of children. This social problem affects the character of children who are getting less and less, judging from the attitudes and behavior of children who are increasingly opposed to parents and even teachers. The way out of this problem requires the role of the family in educating children, because education first and foremost starts from within the family. The purpose of writing this article is to examine, about family education in an effort to build children's character at school.